Development of EM Simulator for Sea Bed Logging Applications using MATLAB - Daud, Hanita (Institut Teknologi Bandung, Indonesia, 2010)
This paper presents a 1D modeling of electromagnetic waves for sea bed environment developed using MATLAB software. This paper focuses on two main areas; the first is on the simulator that is able to model plane layer modeling of the sea bed environment, by setting the deep of sea water, sediments and size and location of the hydrocarbon trap. This model shall be used as a forward modeling of sea bed environment. The second focus is on the effect of electromagnetic waves called direct waves, reflected waves and refracted waves on the sea bed environment where potential hydrocarbon is present. Our work is based on Sea Bed Logging (SBL) application that uses marine controlled source electromagnetic (CSEM) sounding technique to detect and characterize hydrocarbon bearing reservoirs in deep water areas. SBL uses a mobile horizontal electric dipole (HED) source called transmitter and an array of seafloor electric field receivers. The transmitter transmits a low frequency electromagnetic signal from 30m - 40m above the sea bed into water layer and to underneath the sea bed. The array of the receivers will receive the signal in the form of direct waves, air waves, reflected waves and refracted waves and is measured in the form of amplitude and phase. These signals depend on the resistivity structure beneath the sea bed. Hydrocarbon is known to have high resistivity value of 30 – 500 Ωm in contrast to sea water layer of 0.5 – 2 Ωm and sediments of 1-2 Ωm. These signals were plotted to show the Electric Field amplitude verses offset (AVO) and comparisons were made